The history of church institutions: a case study of Nyahuni Adventist High School from 1987-2015 - Magwenzi, Kudakwashe Jonah (Midlands State University, 2017)
The study examines the history of church institutions in Zimbabwe with special reference to Nyahuni Adventist high school in Murewa Mashonaland east province. The aim of the study is to unpack the reasons for the establishment of these church institutions and how they are contributing to the development of the communities around them. The research brought out the main objectives and aims of these church institutions and the measures t hey are implementing in achieving their desired goals. It also revealed how they have succeeded in their quest to develop and help their communities.